A stoichiometrical and ultrastructural study on cell membrane damage by bile salt using human red blood cells - TAO, Seishi; YAMASHITA, Gunji; YAMAMOTO, Masao; SAGAWA, Hiroshi; TAZUMA, SUSUMU; AIHARA, Naoki; KAJIYAMA, Goro; HATSUSHIKA, Sumie; HORIUCHI, Itaru; SASAKI, Harutoshi; MIZUNO, Shigeki (Tando, 1991)
A study on cell membrane damage by bile salts was performed using human red blood cells (RBC). Taurochenodeoxycholate (TCDC), taurodeoxycholate (TDC), taurocholate (TC), and tauroursodeoxycholate (TUDC) were co-incubated with human RBC, respectively, followed by measurement of release of cell free hemoglobin and morphological determination by transmission electron microscopy (TEM). The hydrophobicity of each bile salt was indexed by the retention time of a reverse phase HPLC. Phosphatidylcholine (PC), cholesterol (CH), albumin, and mucin were tested for their ability to protect RBC' from damage by bile salts. Results were as follows; 1. The ranking of hemolytic effects of bile salt determined in stoichiometry and morphology was TDC> TCDC> TC> TUDC.2. A strong linear correlation between hemolytic effects of bile salt and their hydrophobicity was found (y=0.689x-0.054, r=0.991).3. PC and albumin reduced bile salt toxicity dose-dependently, but did neither CH nor mucin. Thus, we deduced that cell membranes including biliary systems are protected against hydrophobic bile salt toxicity by PC and certain proteins, i. e. albumin.